2021
DOI: 10.1186/s13287-021-02389-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and exosomes: promising candidates for necrotizing enterocolitis therapy

Abstract: Necrotizing enterocolitis (NEC) is a devastating disease predominately affecting neonates. Despite therapeutic advances, NEC remains the leading cause of mortality due to gastrointestinal conditions in neonates. Stem cells have been exploited in various diseases, and the application of different types of stem cells in the NEC therapy is explored in the past decade. However, stem cell transplantation possesses several deficiencies, and exosomes are considered potent alternatives. Exosomes, especially those deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…These therapies still need to be refined in clinical trials before they can be widely used in the clinical setting. The current hot topic is the treatment of NEC with various stem cells (bone marrow mesenchymal stem cells, amniotic fluid stem cells, and umbilical cord blood stem cells) and their exosomes, in addition to the treatment of NEC using breast milk exosomes mentioned above [ 132 ]. Recent studies have also identified some new therapeutic pathways and targets.…”
Section: Treatment Of Necmentioning
confidence: 99%
“…These therapies still need to be refined in clinical trials before they can be widely used in the clinical setting. The current hot topic is the treatment of NEC with various stem cells (bone marrow mesenchymal stem cells, amniotic fluid stem cells, and umbilical cord blood stem cells) and their exosomes, in addition to the treatment of NEC using breast milk exosomes mentioned above [ 132 ]. Recent studies have also identified some new therapeutic pathways and targets.…”
Section: Treatment Of Necmentioning
confidence: 99%
“…A meta-analysis including nine animal experiments suggested that stem cells and stem cell-derived exosomes decreased the morbidity of NEC, particularly stage 2 NEC by enhancing intestinal motility and reducing intestinal permeability (Villamor-Martinez et al 2020 ; Walsh et al 1988 ) (Table 1 ). Current research indicates that ISCs, MSCs, and NSCs, which are derived from various tissues, are most commonly used for NEC treatment (Li et al 2022 ; Zhou et al 2013 ; Zeng et al 2021 ; Drucker et al 2018a ). In the subsequent sections, we discuss how stem cells treat NEC as well as their advantages and disadvantages in the clinical setting (Table 2 ).…”
Section: Stem Cell Therapy In Necmentioning
confidence: 99%
“…Human amniotic fluid stem cells (AFSCs) and breast milk (HBM) are hot topics in NEC treatment, and their effects on NEC have been confirmed [ 3 , 4 ]. Studies have shown that amniotic fluid-derived mesenchymal stem cells and neural stem cells can protect NEC intestines from injury [ 5 ]. Randomized trials demonstrated that breast-feeding reduced the incidence of NEC in preterm infants compared with formula feeding [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%